(untitled) (Nigerian Journal of Technology, 2018)
The rise in the failure of mechanical components, some of which are attributable to poor weld joints has given rise to research study on the optimization of weld joint strengths. The quality of welds is highly dependent on the right combination of input process parameters. Irrespective of the welding process, the need for the right combination of input process parameters cannot be over emphasized. To achieve a desired weld quality, the weld features such bead geometry and the mechanical properties were examined and related to the weld input parameters. The Response Surface Methodology (RSM) was used to predict and optimize the weld strength properties (tensile strength and hardness) of a Gas Tungsten Arc Welded 10mm thick mild steel plate. Model adequacy checks, was done using analysis of variance (ANOVA) and found to be adequate. The ANOVA showed that current and gas flow rate had the most significant effect on the tensile strength, but on the Hardness, the gas flow rate and filler rod had the most significant effect. The model F-value of 12.69 at a P value of 0.0001 for the tensile strength and F-value of 8.51 at a P value of 0.0001 for the hardness, showed the significance of the model employed. The optimal tensile strength of 497.555N/mm2 and Hardness of 192.556BHN was observed at a current of 170.12 amp, voltage of 19.84 volt, gas flow rate of 23.92 l/min and filler rod diameter of 2.4mm. http://dx.doi.org/10.4314/njt.v37i2.15